Patellar luxation in dogs. (2nd June 2019) - Lopez de la oliva Cases, Paula; Grierson, James
Abstract : Patellar luxation is one of the most common orthopaedic diseases in dogs. Medial luxation occurs more frequently than lateral, and females and small-breed dogs are overrepresented. Diagnosis can be achieved with a simple orthopaedic examination, but the use of imaging is essential to determine what deformities have caused the patellar luxation and therefore aid planning surgical intervention. Surgery is recommended in patients that are clinically affected and is normally a combination of trochleoplasty, tibial tuberosity transposition and imbrication techniques. The prognosis is generally favourable following surgery, although surgery does not prevent the progression of osteoarthritis.